Factors influencing women’s attitudes towards antenatal vaccines, Group B Streptococcus and clinical trial participation in pregnancy: an on-line survey - McQuaid, F; Jones, C; Stevens, Z; Voysey, M; Snape, M (BMJ Publishing Group, 2016)

(untitled)
Objectives To explore factors influencing the likelihood of antenatal vaccine acceptance of both routine UK antenatal vaccines (influenza and pertussis) and a hypothetical group B Streptococcus (GBS) vaccine in order to improve understanding of how to optimise antenatal immunisation acceptance, both in routine use and clinical trials. Setting An online survey distributed to women of childbearing age in the UK. Participants 1013 women aged 18–44 years in England, Scotland and Wales. Methods Data from an online survey conducted to gauge the attitudes of 1013 women of childbearing age in England, Scotland and Wales to antenatal vaccination against GBS were further analysed to determine the influence of socioeconomic status, parity and age on attitudes to GBS immunisation, using attitudes to influenza and pertussis vaccines as reference immunisations. Factors influencing likelihood of participation in a hypothetical GBS vaccine trial were also assessed. Results Women with children were more likely to know about each of the 3 conditions surveyed (GBS: 45% vs 26%, pertussis: 79% vs 63%, influenza: 66% vs 54%), to accept vaccination (GBS: 77% vs 65%, pertussis: 79% vs 70%, influenza: 78% vs 68%) and to consider taking part in vaccine trials (37% vs 27% for a hypothetical GBS vaccine tested in 500 pregnant women). For GBS, giving information about the condition significantly increased the number of respondents who reported that they would be likely to receive the vaccine. Health professionals were the most important reported source of information. Conclusions Increasing awareness about GBS, along with other key strategies, would be required to optimise the uptake of a routine vaccine, with a specific focus on informing women without previous children. More research specifically focusing on acceptability in pregnant women is required and, given the value attached to input from healthcare professionals, this group should be included in future studies.